Experimental and Theoretical Insights on Chemopreventive Effect of the Liposomal Thymoquinone Against Benzo[a]pyrene-Induced Lung Cancer in Swiss Albino Mice - Khan A; Alsahli MA; Aljasir MA; Maswadeh H; Mobark MA; Azam F; Allemailem KS; Alrumaihi F; Alhumaydhi FA; Almatroudi AA; AlSuhaymi N; Khan MA (Dove Medical Press, 2022)
Arif Khan,1 Mohammed A Alsahli,2 Mohammad A Aljasir,2 Hamzah Maswadeh,3 Mugahid A Mobark,4,5 Faizul Azam,6 Khaled S Allemailem,2 Faris Alrumaihi,2 Fahad A Alhumaydhi,2 Ahmad A Almatroudi,2 Naif AlSuhaymi,7 Masood A Khan1 1Department of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia; 2Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia; 3Department of Pharmaceutics, College of Pharmacy, Qassim University, Buraydah, 51452, Saudi Arabia; 4Department of Pharmacy Practice, College of Pharmacy, Qassim University, Buraydah, 51452, Saudi Arabia; 5Department of Pathology, Faculty of Medicine, University of Kordofan, El-Obeid, Sudan; 6Department of Pharmaceutical Chemistry and Pharmacognosy, Unaizah College of Pharmacy, Qassim University, Unaizah, 51911, Saudi Arabia; 7Department of Emergency Medical Services, Faculty of Health Sciences, AlQunfudah, Umm Al-Qura University, Makkah, 21912, Saudi ArabiaCorrespondence: Arif Khan, Department of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia, Tel +966 590038460, Fax +966 63801628, Email 4140@qu.edu.saPurpose: Thymoquinone (TQ), a phytoconstituent of Nigella sativa seeds, has been studied extensively in various cancer models. However, TQ's limited water solubility restricts its therapeutic applicability. Our work aims to prepare the novel formulation of TQ and assess its chemopreventive potential in chemically induced lung cancer animal model.Methods: The polyethylene glycol coated DOPE/CHEMS incorporating TQ-loaded pH-sensitive liposomes (TQPSL) were prepared and characterized. Mice were exposed to benzo[a]pyrene (BaP) thrice a week for 4 weeks to induce lung cancer. TQPSL was administered three times a week for 21 weeks, starting 2 weeks before the first dose of BaP.Results: The prepared TQPSL revealed 85% entrapment efficiency with 128 nm size and − 19.5 mv ζ-potential showing high stability of the formulation. The pretreatment of TQPSL showed the recovery in BaP-modulated relative organ weight of lungs, cancer marker enzymes, and antioxidant enzymes in the serum. The histopathological analysis of the tissues showed that TQPSL protected the malignancy in the lungs. The flow cytometry data revealed the induction of apoptosis and decreased intracellular ROS by TQPSL. Molecular docking was performed to predict the TQ's affinity for eight possible anticancer drug targets linked to lung cancer etiology. The data assisted to identify the serine/threonine-protein kinase BRAF as the most suitable target of TQ with binding energy − 6.8 kcal/mol.Conclusion: The current findings demonstrated the potential of TQPSL and its possible therapeutic targets of lung cancer. To our knowledge, this is the first research to outline the development of TQ formulation against lung cancer considering its low solubility as well as pulmonary delivery challenges.Keywords: thymoquinone, pH-sensitive liposomes, lung cancer model, molecular docking